2009
DOI: 10.1021/ie801646y
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Thermal Degradation of Poly(methyl methacrylate), Poly(butyl acrylate), and Their Copolymers

Abstract: The photocatalytic and thermal degradations of poly(methyl methacrylate), poly(butyl acrylate), and their copolymers of different compositions were studied. The photocatalytic degradation was investigated in o-dichlorobenzene in the presence of two different catalysts, namely, Degussa P-25 and combustion synthesized nanotitania (CSN-TiO2). The samples were analyzed by using gel permeation chromatography (GPC) to obtain the molecular weight distributions (MWDs) as a function of reaction time. Experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Moreover, biodegradable materials demand more stringent storage conditions [13,14]. The photochemical activities of polymers can be increased by the addition of photocatalysts [15][16][17]. Shang et al [15] incorporated TiO 2 nanoparticles into polystyrene (PS) plastics and achieved a 22.5 % weight loss under 150 h of ultraviolet (UV) light irradiation, whereas without the addition of TiO 2 nanoparticles, the weight loss was only 12.0 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, biodegradable materials demand more stringent storage conditions [13,14]. The photochemical activities of polymers can be increased by the addition of photocatalysts [15][16][17]. Shang et al [15] incorporated TiO 2 nanoparticles into polystyrene (PS) plastics and achieved a 22.5 % weight loss under 150 h of ultraviolet (UV) light irradiation, whereas without the addition of TiO 2 nanoparticles, the weight loss was only 12.0 %.…”
Section: Introductionmentioning
confidence: 99%
“…The photochemical activities of polymers can be increased by the addition of photocatalysts [15][16][17]. Shang et al [15] incorporated TiO 2 nanoparticles into polystyrene (PS) plastics and achieved a 22.5 % weight loss under 150 h of ultraviolet (UV) light irradiation, whereas without the addition of TiO 2 nanoparticles, the weight loss was only 12.0 %. Zhao et al [18] introduced TiO 2 nanoparticles into PE to form a complex film that showed a high photocatalytic activity under UV light and sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…3. The homopolymer PBA's end groups which were generated by the adopted initiator had a great influence on its thermal degradation; thus the homopolymers of BA synthesized by different initiators began to degrade at different temperatures, ranging from 250 to 320°C [26][27][28][29][30][31]. However, we found from TG curves that the fibrous membranes did not degrade at the temperature below 380°C; additionally, the DTG curve of each fibrous membrane showed only one peak.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…This is a striking advantage for both classical polymerization of monofunctional monomers and modern curing applications. The polymerization of vinyl monomers sensitized by inorganic photoinitiators in the presence of an electron donor compound has attracted much attention [19][20][21][22][23][24][25]. Many of studies involved the use of compounds of Ti [19,20], Ru [21], Co [22], etc.…”
Section: Introductionmentioning
confidence: 99%